Visual hydrochromic sensing material as well as preparation method and application thereof
By setting the metal membrane layer, semiconductor gas -sensitive membrane layer and nano catalyst layer in the middle layer of hydrogen sensing material, the problem of high temperature power consumption and visual consumption of existing hydrogen sensing technology has been solved. Hydrogen detection and visualization effect.
Patent Information
- Application Number
- CN202411517785.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
AI Technical Summary
In the existing hydrogen sensing technology, sensors based on metal oxide semiconductors need to operate at high temperatures, which increases power consumption and use complexity, and the visibility of existing hydrogen-chromic materials is limited.
Provide a color -changing sensor material, including the substrate, metal membrane layer, semiconductor gas -sensitive membrane layer, and nano -catalyst layer of the semiconductor gas -sensitive membrane layer in order Disposal mode-cavity mode coupling to realize the visual detection of hydrogen.
Realize the efficient, fast, and sensitive hydrogen detection, have colorful structural colors, change significantly before and after hydrogen absorption, it is easy to prepare and operate in large areas, and it is suitable for industrialized applications.
Smart Images

Figure CN119372646A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of gas sensing technology, and in particular to a visual hydrogen-induced color-changing sensing material and a preparation method and application thereof. Background Art
[0002] Hydrogen is a key gas widely used in industry, energy and chemistry. It is regarded as one of the ideal energy sources of the future because of its non-toxic, clean and renewable characteristics. However, the explosion limit of hydrogen in the air is wide (4-74 vol%), the ignition temperature is low, and it is prone to leakage and explosion accidents. Therefore, the detection and monitoring of hydrogen is of great significance. Existing hydrogen sensing technologies mainly include electrochemical sensors, metal oxide semiconductor sensors and optical sensors. Among them, hydrogen sensors based on metal oxide semiconductors (such as WO3) have been widely studied and applied due to their high sensitivity and selectivity. However, traditional metal oxide semiconductor sensors usually need to work at high temperatures, which increases the power consumption and complexity of the sensor, limiting its scope of application.
[0003] In recent years, hydrogen-induced chromic materials have attracted widespread attention due to their ability to change color in the presence of hydrogen. This material can not only detect hydrogen, but also achieve visual detection through color change. It is easy to operate and easy to achieve rapid on-site detection. However, existing hydrogen-induced chromic materials are usually based on the intrinsic color of semiconductor gas-sensitive films, and their visibility is very limited. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a visualized hydrogen chromic sensing material and a preparation method and application thereof. The hydrogen chromic sensing material provided by the present invention has a high degree of visualization.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a visualized hydrogen-induced color-changing sensing material, comprising a substrate, a metal film layer, a semiconductor gas-sensitive film layer and a nano catalyst layer which are stacked in sequence.
[0007] Preferably, the thickness of the metal film layer is 5 to 2000 nm.
[0008] Preferably, the elements in the metal film layer include one or more of Cr, Mo, Ti, W, Au, Ag, Pt, Pd, Cu and Al.
[0009] Preferably, the thickness of the semiconductor gas-sensitive film layer is 1 to 1000 nm.
[0010] Preferably, the semiconductor gas-sensitive film layer includes one or more of a WO3 film, a MoO3 film and a VO2 film.
[0011] Preferably, the WO3 film is further doped with one or more of Ti, Mo and V, the MoO3 film is further doped with one or more of Ti, W and V, and the VO2 film is further doped with one or more of Ti, W and Mo.
[0012] Preferably, the nano catalyst layer is a nano particle layer or a nano film layer, the particle size of the nano particles in the nano particle layer is 1 to 100 nm, and the thickness of the nano film layer is 0.1 to 50 nm.
[0013] Preferably, the elements in the nano catalyst layer include one or more of Pt, Pd, Au, Ag, Rh, Ru, Cu, Ti and Ni.
[0014] The present invention also provides a method for preparing the visualized hydrogen-induced color-changing sensing material described in the above technical solution, comprising the following steps:
[0015] Deposition is performed on the surface of the substrate to sequentially form the metal film layer, the semiconductor gas-sensitive film layer and the nano-catalyst layer to obtain the visualized hydrogen-induced color-changing sensing material.
[0016] The present invention also provides the application of the visualized hydrogen-induced color-changing sensing material described in the above technical solution in the field of gas sensors.
[0017] The invention provides a visualized hydrogen-induced color-changing sensing material, comprising a substrate, a metal film layer, a semiconductor gas-sensitive film layer and a nano catalyst layer which are stacked in sequence.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) Visual detection: The visualized hydrogen chromic sensing material of the present invention has structural color itself. The structural color comes from the coupling of the plasmon mode of the nanoparticles in the nanocatalyst layer in the material and the cavity mode in the semiconductor-metal film. This strong coupling causes the material to have selective light absorption, which presents a specific color on a macro scale. The coupling mode in the material is very sensitive to the change of the dielectric constant of the semiconductor gas-sensitive film layer, and hydrogen absorption can cause the dielectric constant of the semiconductor gas-sensitive film layer to change. A slight change in the dielectric constant can cause a significant change in the structural color of the material, and a very obvious color change before and after hydrogen absorption can be visualized on a macro scale, which is convenient for intuitive visual detection. In addition, the visualized hydrogen chromic sensing material of the present invention has rich and colorful structural colors. Unlike the existing semiconductor hydrogen chromic thin films, the structural color of the visualized hydrogen chromic sensing material of the present invention has a high degree of visualization itself, and the change before and after hydrogen absorption is significant, so the degree of visualization is high. In addition, the structural color can be adjusted by adjusting the material parameters (such as the thickness or dielectric constant of the semiconductor gas-sensitive film layer).
[0020] (2) Short response time: In traditional hydrogen-induced color-changing films, the color-changing mechanism mainly comes from the diffusion of hydrogen atoms into the semiconductor lattice. The semiconductor oxide plunders the electrons of the hydrogen atoms, causing the metal atoms in the semiconductor to transition back and forth between different valence states, resulting in light absorption. To achieve considerable light absorption and thus cause color change, the number of hydrogen atoms entering the lattice must be sufficient. The color-changing mechanism of the visualized hydrogen-induced color-changing sensing material of the present invention is: the change in the dielectric constant of the semiconductor gas-sensitive film layer after hydrogen absorption. A small amount of hydrogen atoms entering the semiconductor gas-sensitive film layer can cause a significant change in the dielectric constant, and the dielectric constant changes rapidly, resulting in the material being able to respond quickly to changes in hydrogen concentration, and the hydrogen absorption and desorption time is short (within 10 seconds), achieving real-time monitoring and observation.
[0021] (3) High sensitivity: Different from the color change mechanism of traditional hydrogen-induced chromic materials, the plasmon mode-cavity mode strong coupling mode supported in the hydrogen-induced chromic material of the present invention is very sensitive to changes in the dielectric constant. This is the essence of the high sensitivity of the material and can achieve hydrogen detection as low as 0.001% concentration.
[0022] (4) Easy to prepare on a large scale: The hydrogen-induced color-changing sensing material adopts a laminated structure design and can be processed by standard thin film deposition and spin coating processes, which is suitable for large-scale production.
[0023] (5) Easy to use and easy to operate: The material structure is simple, the detection process does not require complex equipment, and is easy to operate.
[0024] The present invention also provides a method for preparing the visualized hydrogen-induced color-changing sensing material described in the above technical solution. The preparation method of the present invention is simple and easy to realize industrial application.
[0025] In summary, the visualized hydrogen chromic sensing material of the present invention has efficient hydrogen chromic performance, a high degree of visualization, can achieve rapid and sensitive hydrogen detection, and is easy to prepare and operate on a large area. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The schematic diagram of the structure of the visualized hydrogen-induced color-changing sensing material of the present invention, wherein 1 is a substrate, 2 is a metal film layer, 3 is a semiconductor gas-sensitive film layer, and 4 is a nano-catalyst layer;
[0027] Figure 2 This is a cross-sectional SEM morphology image of the visualized hydrogen-induced color-changing sensing material obtained in Example 1;
[0028] Figure 3 This is a low-magnification STEM morphology image of the surface Pt nanoparticles in the visualized hydrogen-induced color-changing sensing material obtained in Example 1;
[0029] Figure 4This is a high-magnification STEM morphology image of the surface Pt nanoparticles in the visualized hydrogen-induced color-changing sensing material obtained in Example 1;
[0030] Figure 5 The reflectance spectrum of the visualized hydrogen-induced color-changing sensing material obtained in Example 3 before and after hydrogen is passed;
[0031] Figure 6 The response curve of the reflectivity of the visualized hydrogen-induced color-changing sensing material obtained in Example 1 at 700 nm as the concentration of hydrogen gas introduced changes;
[0032] Figure 7 The response curve of the reflectivity of the visualized hydrogen-induced color-changing sensing material obtained in Example 2 at 700 nm as the concentration of hydrogen introduced changes;
[0033] Figure 8 The response curve of the reflectivity of the visualized hydrogen-induced color-changing sensing material obtained in Example 3 at 700 nm as a function of the concentration of hydrogen introduced;
[0034] Fig. 9 (a) is the transmission spectrum of the visualized hydrogen chromic sensing material obtained in Comparative Example 1 before and after hydrogen is passed, and (b) is the response curve of the light absorption rate of the visualized hydrogen chromic sensing material obtained in Comparative Example 1 at 700nm as the concentration of hydrogen passed changes. DETAILED DESCRIPTION
[0035] The invention provides a visualized hydrogen-induced color-changing sensing material, comprising a substrate, a metal film layer, a semiconductor gas-sensitive film layer and a nano catalyst layer which are stacked in sequence.
[0036] Figure 1 The schematic diagram of the structure of the visualized hydrogen-induced color-changing sensing material of the present invention, wherein 1 is a substrate, 2 is a metal film layer, 3 is a semiconductor gas-sensitive film layer, 4 is a nano-catalyst layer, and the following is combined with Figure 1 The visualized hydrogen color-changing sensing material of the present invention is described.
[0037] The visualized hydrogen chromic sensing material of the present invention comprises a substrate 1 .
[0038] The present invention has no special limitation on the thickness of the substrate 1 , and any thickness known to those skilled in the art may be used.
[0039] In the present invention, the material of the substrate 1 is preferably an insulator, a semiconductor, a silicon-on-insulator material (SOI), a composite material of SOI, silicon and metal, a metal or a polymer. The insulator is preferably glass, quartz (SiO2) or ceramic, and the ceramic is more preferably alumina; the semiconductor is preferably silicon, GaN or GaAs; the metal is preferably aluminum, stainless steel or an aluminum alloy; the polymer is preferably silicone, polyvinyl alcohol (PVA), polyethylene terephthalate (PET), polyimide (PI), polyethylene naphthalate (PEN), polydimethylsiloxane (PDMS) or polytetrafluoroethylene (PTFE).
[0040] The visualized hydrogen-induced color-changing sensing material of the present invention comprises a metal film layer 2 .
[0041] In the present invention, the thickness of the metal film layer 2 is preferably 5 to 2000 nm, and specifically may be 100, 200, 300, 500, 1000, 1500 or 2000 nm.
[0042] In the present invention, the elements in the metal film layer 2 preferably include one or more of Cr, Mo, Ti, W, Au, Ag, Pt, Pd, Cu and Al.
[0043] In the present invention, the material of the metal film layer 2 is preferably an alloy or a metal mixture, the alloy is preferably an alloy formed by two or more elements of Cr, Mo, Ti, W, Au, Ag, Pt, Pd, Cu and Al, and the metal mixture is preferably a mixture formed by two or more elements of Cr, Mo, Ti, W, Au, Ag, Pt, Pd, Cu and Al.
[0044] In the present invention, the thickness of the semiconductor gas-sensitive film layer 3 is preferably 1-1000 nm, and specifically can be 100, 200, 300, 350, 500 or 1000 nm.
[0045] In the present invention, the semiconductor gas-sensitive film layer 3 preferably includes one or more of a WO3 film, a MoO3 film and a VO2 film. When the semiconductor gas-sensitive film layer 3 preferably includes multiple of a WO3 film, a MoO3 film and a VO2 film, the semiconductor gas-sensitive film layer 3 is a composite gas-sensitive film, and the composite gas-sensitive film is preferably MoO3-WO3.
[0046] In the present invention, the WO3 film is preferably doped with one or more of Ti, Mo and V, the MoO3 film is preferably doped with one or more of Ti, W and V, and the VO2 film is preferably doped with one or more of Ti, W and Mo. The present invention has no particular limitation on the content of the doping elements in the semiconductor gas-sensitive film layer 3, and the content well known to those skilled in the art can be used.
[0047] In the present invention, the nanocatalyst layer 4 is preferably a nanoparticle layer or a nanofilm layer. The particle size of the nanoparticles in the nanoparticle layer is preferably 1 to 100 nm, specifically 1, 6, 10, 12, 50 or 100 nm. The thickness of the nanofilm layer is preferably 0.1 to 50 nm.
[0048] In the present invention, the elements in the nano catalyst layer 4 preferably include one or more of Pt, Pd, Au, Ag, Rh, Ru, Cu, Ti and Ni.
[0049] In the present invention, the material of the nanocatalyst layer 4 is preferably an alloy or a metal mixture, the alloy is preferably an alloy formed by two or more elements of Pt, Pd, Au, Ag, Rh, Ru, Cu, Ti and Ni, more preferably Pt-Pd alloy nanoparticles, and the metal mixture is preferably a mixture formed by two or more elements of Pt, Pd, Au, Ag, Rh, Ru, Cu, Ti and Ni.
[0050] The present invention also provides a method for preparing the visualized hydrogen-induced color-changing sensing material described in the above technical solution, comprising the following steps:
[0051] Deposition is performed on the surface of the substrate to sequentially form the metal film layer, the semiconductor gas-sensitive film layer and the nano-catalyst layer to obtain the visualized hydrogen-induced color-changing sensing material.
[0052] In the present invention, the deposition method for forming the metal film layer 2 preferably includes physical vapor deposition, chemical vapor deposition, atomic layer deposition or electroplating.
[0053] In the present invention, the deposition method for forming the semiconductor gas-sensitive film layer 3 preferably includes physical vapor deposition, chemical vapor deposition, atomic layer deposition, sol-gel method or solvent thermal reaction method.
[0054] In the present invention, the deposition method for forming the nano catalyst layer 4 preferably includes physical vapor deposition, chemical vapor deposition, atomic layer deposition, solvent reaction method or gas aggregation method.
[0055] The present invention has no particular limitation on the specific parameters of the deposition, and a method familiar to those skilled in the art may be used.
[0056] The present invention also provides the application of the visualized hydrogen-induced color-changing sensing material described in the above technical solution in the field of gas sensors.
[0057] The present invention has no particular limitation on the specific manner of the application, and any manner familiar to those skilled in the art may be used.
[0058] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] Example 1
[0060] A method for preparing a visual hydrogen-induced color-changing sensing material comprises the following steps:
[0061] (1) depositing a metal film layer on the surface of the substrate;
[0062] Quartz (SiO2) was selected as the substrate, and a Pt metal film layer with a thickness of 100 nm was deposited on the surface of the substrate by electron beam evaporation.
[0063] (2) electron beam evaporation is used to deposit a semiconductor gas-sensitive film layer on the surface of the Pt metal film layer. The semiconductor gas-sensitive film layer is WO3 with a film thickness of 200 nm;
[0064] (3) A nanocatalyst layer is deposited on the surface of the semiconductor gas-sensitive film layer WO3 by using a gas phase cluster beam deposition technique. The nanocatalyst layer is Pt nanoparticles, and the average size of the Pt nanoparticles is 6 nm, that is, the thickness of the nanocatalyst layer is 6 nm.
[0065] Example 2
[0066] A method for preparing a visual hydrogen-induced color-changing sensing material comprises the following steps:
[0067] (1) depositing a metal film layer on the surface of the substrate;
[0068] Silicon was selected as the substrate, and a Ag metal film layer was deposited on the surface of the substrate by thermal evaporation method with a film thickness of 200nm.
[0069] (2) Electron beam evaporation is used to deposit a semiconductor gas-sensitive film layer on the surface of the Ag metal film layer. The semiconductor gas-sensitive film layer is Ti x WO3, film thickness is 300nm;
[0070] (3) The nanocatalyst layer is deposited on the semiconductor gas-sensitive film layer Ti by using gas phase cluster beam deposition technology. x On the surface of WO3, the nano catalyst layer is Pd nano particles, and the average size of the Pd nano particles is 10 nm, that is, the thickness of the nano catalyst layer is 10 nm.
[0071] Example 3
[0072] A method for preparing a visual hydrogen-induced color-changing sensing material comprises the following steps:
[0073] (1) depositing a metal film layer on the surface of the substrate;
[0074] PET was selected as the substrate, and an Al metal film layer was deposited on the surface of the substrate by magnetron sputtering with a film thickness of 300 nm.
[0075] (2) depositing a semiconductor gas-sensitive film layer on the surface of the Al metal film layer by electron beam evaporation, wherein the semiconductor gas-sensitive film layer is a MoO3-WO3 composite film, wherein the MoO3 film thickness is 100 nm, the WO3 film thickness is 250 nm, and the total thickness of the MoO3-WO3 composite film is 350 nm;
[0076] (3) A nanocatalyst layer is deposited on the surface of the semiconductor gas-sensitive membrane layer MoO3-WO3 composite film by using gas phase cluster beam deposition technology. The nanocatalyst layer is Pt-Pd alloy nanoparticles, and the average size of the Pt-Pd nanoparticles is 12nm, that is, the thickness of the nanocatalyst layer is 12nm.
[0077] Comparative Example 1
[0078] A quartz substrate was selected, and a WO3 thin film was prepared on the surface of the substrate by electron beam evaporation, and then Pt nanoparticles were deposited on the surface of the WO3 thin film by gas phase cluster beam deposition technology, the thickness of WO3 was 200nm, and the average size of the Pt nanoparticles was 6nm. The difference from Example 1 is that the Pt metal film is not prepared on the surface of the quartz substrate, and the rest is the same as Example 1.
[0079] Figure 2 This is the SEM cross-sectional morphology of the visualized hydrogen-induced color-changing sensing material obtained in Example 1. It can be seen that the Pt metal film layer is located on the surface of the SiO2 substrate, the WO3 semiconductor gas-sensitive film layer is located on the surface of the Pt metal film layer, and the Pt nanocatalyst layer is located on the surface of the WO3 semiconductor gas-sensitive film layer.
[0080] Figure 3 This is a low-magnification STEM image of the Pt nanocatalyst layer in Example 1. It can be seen that the metal nanoparticle catalyst layer is composed of Pt nanoparticles, and the average size of the nanoparticles is 6 nm.
[0081] Figure 4 This is a high-magnification STEM image of the Pt nanoparticle catalyst layer in Example 1. It can be seen that the Pt nanoparticle catalyst layer has good monodispersity and it can be clearly seen from the lattice fringes that the Pt nanoparticles are crystalline.
[0082] The visualized hydrogen-induced color-changing sensing materials obtained in Examples 1 to 3 and Comparative Example 1 were placed in a test cavity, and an air-hydrogen mixed gas was introduced. The gas pressure in the cavity was maintained at 1 atmosphere. The concentration of hydrogen could be adjusted arbitrarily by controlling the flow rate of the gas flowmeter. All reflection and transmission spectra and hydrogen response curves at a single wavelength were measured by a grating spectrometer.
[0083] Figure 5 The reflection spectrum of the hydrogen-induced color-changing sensing material before and after the hydrogen-air mixture is introduced is visualized in Example 3, and the hydrogen concentration is 2000ppm. It can be seen from the spectrum that the reflection peak and absorption peak of the material are significantly blue-shifted after the hydrogen-air mixture is introduced, and the absorption of the material is also significantly increased after the hydrogen is introduced.
[0084] Figure 6 This is the response curve of the single-wavelength light absorbance of the visualized hydrogen chromic sensing material obtained in Example 1 at a wavelength of 700nm as a function of hydrogen concentration. The hydrogen concentration varies from 1000 to 14000ppm, and the color of the material changes significantly accordingly - from green to dark purple. The illustration shows the actual effect of the material changing color when 5000ppm of hydrogen is introduced. It can be seen that the hydrogen chromic material has a significant color change effect and a high degree of visualization.
[0085] Figure 7 The response curve of the single wavelength light absorption rate of the visualized hydrogen-induced color-changing sensing material obtained in Example 2 at a wavelength of 700nm as a function of hydrogen concentration. The range of hydrogen concentration is 1000-18000ppm, and the color of the material also changes significantly accordingly - from red to yellow. The illustration shows the actual effect of the material changing color when 1000ppm of hydrogen is introduced. It can be seen that the color-changing effect of the hydrogen-induced color-changing material is obvious and the degree of visualization is high.
[0086] Figure 8 This is the response curve of the single-wavelength light absorbance of the visualized hydrogen chromic sensing material obtained in Example 3 at a wavelength of 700nm as a function of hydrogen concentration. The hydrogen concentration varies in the range of 2000 to 10000ppm, and the color of the material also changes significantly accordingly - from light purple to dark purple. The illustration shows the actual effect of the material changing color when 2000ppm of hydrogen is introduced. It can be seen that the color change effect of the hydrogen chromic material is obvious and the degree of visualization is high.
[0087] Comparing the visualized hydrogen chromic sensing materials obtained in Examples 1 to 3, it can be found that the visualized hydrogen chromic sensing materials obtained have different structural colors when the preparation parameters of the materials are different. The difference in structural colors is due to the different light absorption of the materials. The light absorption of the visualized hydrogen chromic sensing material of the present invention is mainly regulated by the thickness of the semiconductor gas-sensitive film layer. The thickness of the semiconductor gas-sensitive film layer is different, the light absorption band of the material is different, and the color of the material is correspondingly different. However, no matter what preparation parameters are used to prepare the material, after hydrogen is introduced, significant hydrogen chromic changes occur, and the degree of visualization is high. This also reflects from another aspect that the hydrogen chromic material of the present invention is not highly dependent on the accuracy of its structural parameters and is easy to prepare, because no matter what parameters are used to prepare the material, although the initial structural colors are not the same, a hydrogen chromic effect with a high degree of visualization can be obtained. In addition, it can be seen from the response curve of single-wavelength light absorption with hydrogen concentration that the hydrogen chromic material of the present invention has obvious light absorption changes in a wide range of hydrogen concentration (1000 to 100000 ppm), which also means that the material is very suitable for preparing hydrogen sensor devices based on light absorption.
[0088] Fig. 9 (a) is the transmission spectrum of the conventional material with good hydrogen-induced color performance prepared in Comparative Example 1 before and after hydrogenation (the concentration of hydrogen gas is 100000ppm). It can be seen that the material itself is transparent and does not have the structural color of the hydrogen-induced color materials in Examples 1 to 3 of the present invention. The transmittance of the material obtained in Comparative Example 1 is significantly reduced after hydrogenation, especially in the longer wavelength range of 600 to 800nm. The transmittance decreases more significantly, indicating that the absorption of the material increases after hydrogenation, and the transparency of the material decreases, and it has a certain visibility. Fig. 9 As can be seen from the illustration in (b), the material does undergo hydrogen-induced discoloration, but the discoloration effect is poor and the degree of visualization is low. Fig. 9 (b) is the response curve of the single wavelength light absorption rate of the hydrogen chromic material obtained in Comparative Example 1 at a wavelength of 700nm as a function of the hydrogen concentration, and the hydrogen concentration varies in the range of 10000 to 200000ppm. It can be seen that when the light absorption changes significantly, the hydrogen concentration is as high as 10000ppm, which is quite different from the hydrogen chromic material of the present invention.
[0089] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A visual hydrogen-induced color-changing sensing material, characterized in that: The invention comprises a substrate, a metal film layer, a semiconductor gas-sensitive film layer and a nano catalyst layer which are stacked in sequence.
2. The visualized hydrogen-induced color-changing sensing material according to claim 1, characterized in that: The thickness of the metal film layer is 5 to 2000 nm.
3. The visualized hydrogen-induced color-changing sensing material according to claim 1 or 2, characterized in that: The elements in the metal film layer include one or more of Cr, Mo, Ti, W, Au, Ag, Pt, Pd, Cu and Al.
4. The visualized hydrogen-induced color-changing sensing material according to claim 1, characterized in that: The thickness of the semiconductor gas-sensitive film layer is 1 to 1000 nm.
5. The visualized hydrogen-induced color-changing sensing material according to claim 1 or 4, characterized in that: The semiconductor gas-sensitive film layer includes one or more of a WO3 film, a MoO3 film and a VO2 film.
6. The visualized hydrogen-induced color-changing sensing material according to claim 5, characterized in that: The WO3 film is further doped with one or more of Ti, Mo and V, the MoO3 film is further doped with one or more of Ti, W and V, and the VO2 film is further doped with one or more of Ti, W and Mo.
7. The visualized hydrogen-induced color-changing sensing material according to claim 1, characterized in that: The nano catalyst layer is a nano particle layer or a nano film layer. The particle size of the nano particles in the nano particle layer is 1-100 nm, and the thickness of the nano film layer is 0.1-50 nm.
8. The visualized hydrogen-induced color-changing sensing material according to claim 1 or 7, characterized in that: The elements in the nano catalyst layer include one or more of Pt, Pd, Au, Ag, Rh, Ru, Cu, Ti and Ni.
9. The method for preparing the visualized hydrogen-induced color-changing sensing material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Deposition is performed on the surface of the substrate to sequentially form the metal film layer, the semiconductor gas-sensitive film layer and the nano-catalyst layer to obtain the visualized hydrogen-induced color-changing sensing material.
10. Use of the visualized hydrogen-induced color-changing sensing material according to any one of claims 1 to 8 in the field of gas sensors.